Surgically Assisted Rapid Maxillary Expansion (SARME) Treatment in a Severe Maxillary Constriction Patient: Case Report - Eren İşman; Sertaç Aksakallı; Sıddık Malkoç (Turkish Journal of Orthodontics, 2011)

(untitled)
The purpose of this article was to apply surgically assisted rapid maxillary expansion in an adult patient who had severe maxillary constriction followed by two maxillary canine impactions for gaining Class I canine-molar relationship and determine the changes before and after treatment. 18,5 years of age Caucasian female was referred to our clinic with the primary complaint of unaesthetic smile and anterior crowding. In model cast analysis, it has been determined that there was 5.1 mm space requirement in mandible and 12.3 mm in maxilla. Overjet was 6.8 mm, overbite was 2.2 mm. The treatment plan consisted of leveling and alignment of maxillary and mandibular teeth after the SARME. An acrylic cap expansion appliance was preferred. Class I canine-molar relationship at the end of the treatment was aimed. After the treatment the maxillary constriction has been eliminated and class I molar relationship was established on both sides. The radiographic evaluation revealed 3.9 mm nasal and 5.2 mm maxillary width widening. The smile esthetic was improved and the malpositions of the teeth were relieved. As a conclusion; SARME is a successful treatment modality for adult patients requiring palatal expansion.